Canadian Agility and Movement Skill Assessment (CAMSA): Validity, objectivity, and reliability evidence for children 8-12 years of age - Patricia E. Longmuir; Charles Boyer; Meghann Lloyd; Michael M. Borghese; Emily Knight; Travis J. Saunders; Elena Boiarskaia; Weimo Zhu; Mark S. Tremblay (Elsevier, 2017)
Purpose: The primary aim of this study was to develop an assessment of the fundamental, combined, and complex movement skills required to support childhood physical literacy. The secondary aim was to establish the feasibility, objectivity, and reliability evidence for the assessment. Methods: An expert advisory group recommended a course format for the assessment that would require children to complete a series of dynamic movement skills. Criterion-referenced skill performance and completion time were the recommended forms of evaluation. Children, 8-12 years of age, self-reported their age and gender and then completed the study assessments while attending local schools or day camps. Face validity was previously established through a Delphi expert (n = 19, 21% female) review process. Convergent validity was evaluated by age and gender associations with assessment performance. Inter- and intra-rater (n = 53, 34% female) objectivity and test-retest (n = 60, 47% female) reliability were assessed through repeated test administration. Results: Median total score was 21 of 28 points (range 5-28). Median completion time was 17 s. Total scores were feasible for all 995 children who self-reported age and gender. Total score did not differ between inside and outside environments (95% confidence interval (CI) of difference: −0.7 to 0.6; p = 0.91) or with/without footwear (95%CI of difference: −2.5 to 1.9; p = 0.77). Older age (p < 0.001, η2 = 0.15) and male gender (p < 0.001, η2 = 0.02) were associated with a higher total score. Inter-rater objectivity evidence was excellent (intraclass correlation coefficient (ICC) = 0.99) for completion time and substantial for skill score (ICC = 0.69) for 104 attempts by 53 children (34% female). Intra-rater objectivity was moderate (ICC = 0.52) for skill score and excellent for completion time (ICC = 0.99). Reliability was excellent for completion time over a short (2-4 days; ICC = 0.84) or long (8-14 days; ICC = 0.82) interval. Skill score reliability was moderate (ICC = 0.46) over a short interval, and substantial (ICC = 0.74) over a long interval. Conclusion: The Canadian Agility and Movement Skill Assessment is a feasible measure of selected fundamental, complex and combined movement skills, which are an important building block for childhood physical literacy. Moderate-to-excellent objectivity was demonstrated for children 8-12 years of age. Test-retest reliability has been established over an interval of at least 1 week. The time and skill scores can be accurately estimated by 1 trained examiner.